Assessment of Agriculture Stakeholder Engagement in GCF and Climate Financing Processes in CARICOM Countries - St. Ville, Lyndell (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
This report assesses the engagement of agricultural stakeholders in Green Climate Fund (GCF) and broader climate change processes in nine Caribbean Community (CARICOM) countries. In particular, weak agricultural expertise within National Designated Authority (NDA) and Accredited Entities (AEs), and negative social and environmental stigma associated with agriculture contribute to limited access to climate funds. The report presents the findings of a mixed-methods approach that involves data from 220 completed online questionnaires and two focus groups. The results state that agricultural stakeholders are generally positive towards climate change financing but remain at lower levels on the stakeholder engagement pyramid, underscoring that more tailored strategies and guidelines are required for stakeholder engagement.